2014
DOI: 10.1136/jnnp-2013-307381
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement and validity of bedside ‘positive signs’ for functional weakness, sensory and gait disorders in conversion disorder: a pilot study

Abstract: Our study confirms that six bedside 'positive signs' are highly specific for CD with good-excellent inter-rater reliability; we propose to consider them as 'highly reliable signs'. In addition 13 signs could be considered as 'reliable signs' and six further signs as 'suggestive signs' while all others should be used with caution until further validation is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 18 publications
(34 reference statements)
3
61
0
3
Order By: Relevance
“…A number of studies have established the reliability of existing signs such as Hoover's sign for functional limb weakness [14,15] and the entrainment test for functional tremor [16]. A particularly useful study showed that such signs not only have reasonable sensitivity and specificity, but also acceptable inter-rater reliability [17]. Additional studies have described new specific clinical and laboratory features, such as accelerometry for functional head tremor, or using reaction time to assess functional dystonia which may assist in positively identifying the diagnosis [18][19][20].…”
Section: Advances In Diagnosis and Classification Of Functional Neuromentioning
confidence: 99%
“…A number of studies have established the reliability of existing signs such as Hoover's sign for functional limb weakness [14,15] and the entrainment test for functional tremor [16]. A particularly useful study showed that such signs not only have reasonable sensitivity and specificity, but also acceptable inter-rater reliability [17]. Additional studies have described new specific clinical and laboratory features, such as accelerometry for functional head tremor, or using reaction time to assess functional dystonia which may assist in positively identifying the diagnosis [18][19][20].…”
Section: Advances In Diagnosis and Classification Of Functional Neuromentioning
confidence: 99%
“…A new criterion (B) requires that 'clinical findings provide evidence for incompatibility between the symptom and recognized neurological or medical conditions' [3,4] (American Psychiatric Association, 2013). The way to provide the evidence for incompatibility is to use bedside tests [5] or paraclinical tests [6] that are specific and reliable for functional neurological disorder (FND) [7,8]. Earlier diagnostic criteria for functional/psychogenic movement disorders, such as the original [9] and modified [10] Fahn and Williams criteria, also emphasized incongruence and incompatibility with a known neurological condition.…”
Section: Diagnosismentioning
confidence: 99%
“…Functional impairment of equilibrium is often accompanied with exaggerated compensatory maneuvers such as putting the arms out ('tightrope walking'), or marked reduction in the step height and stride length ('walking on ice') [44]. These following signs have a high specificity (between 94 and 100%): momentary fluctuations of stance and gait, excessive slowness or hesitation, psychogenic Romberg test, uneconomic postures, 'walking on ice,' and sudden buckling of the knees [8,45]. 'Huffing and puffing' signs (huffing, grimacing, and breath holding while walking) were present in 44% of patients with functional gait disorders, but minimal or absent in organic gait disorder, yielding 89-100% specificity [46].…”
Section: Gaitmentioning
confidence: 99%
“…Conversion disorder remains a diagnosis of exhaustive exclusion as it lacks established pathophysiology, biomarkers and imaging correlates. Positive clinical signs are only now being validated 5 6. The incidence is historically approximated to be 4–12 cases per 100 000 per year 7…”
Section: Introductionmentioning
confidence: 99%